Settlement of Title Transfer Process For Sale and Purchase of Certified Land with Unknown Seller in Tulungagung Regency (Case Study of Decision Number 18/Pdt.G/2024/PN Tlg) - Mawaddah, Elisa; Navisa, Fitria Dewi; Sunardi, Sunardi (Dinasti Research, 2025)
The objective of this study is to investigate how the process of changing the name of the sale and purchase of certified land is resolved in Tulungagung Regency when the seller's location is unknown, using Decision Number 18/Pdt.G/2024/PN Tlg as a case study. In this research, normative legal methods are employed, incorporating statutory and case analysis, and drawing on sources such as laws, legal principles, and judicial rulings. The findings indicated that even though the sale was carried out without a formal Sale and Purchase Deed, the court ruling effectively validated the transaction. This ruling enables the buyer or their successors to transfer the certificate of title at the National Land Agency. It demonstrates that the legal system can provide assurance to honest individuals involved in land transactions. The study highlights the significance of the judiciary in addressing bureaucratic hurdles concerning land ownership and stresses the importance of public legal education to ensure compliance with regulations when purchasing or selling land.